Analisis Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Pt Iskandar Indah Printing Tekstil Surakarta - Purwanto, Dimas Dwi, Drs. Makruf, MM (2017)
This study aimed to analyze the influence of motivation and discipline on the performance of employees of PT Iskandar Indah Printing Textile Surakarta. The method used for the retrieval of samples in this study uses primary data from respondents can be in the form of questionnaires and interviews of employees of PT Iskandar Indah Printing Textile Surakarta were 116 respondents were sampled in this study. The instrument used to test the feasibility of a question within the questionnaire are validity and reliability. For the method of data analysis used in this study is a t-test and permanence test model (the F test and R ^ 2) which shows the result of the influence of motivation and discipline against employees' performance significantly. From this research it is known that the motivation and discipline of work has a significant influence on employee performance in PT Iskandar Indah Printing textiles partially or jointly. Motivation is the most influential variable on employee performance directed by t test of 3.312. Labor discipline significantly influence employee performance directed by t test of 3.206. Motivation and discipline together significantly affect the performance of employees devoted to the F test results of 14.593 while the performance variation explained by the variable employee motivation and discipline of 40.4% while the rest influenced by other variables. From the above data it can be concluded that the motivation variable is the variable most dominant influence on the performance of employees of PT Iskandar Indah Printing textile Surakarta.